2017
DOI: 10.12681/bgsg.11867
|View full text |Cite
|
Sign up to set email alerts
|

The Samothrace Earthquake of May 2014 and the Displacements Estimations Using Permanent GPS Stations Data

Abstract: The contribution of GPS networks in monitoring seismic events is important because they can provide a direct geometrical information on the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…The analysis of the GPS data from the stations in the North Aegean Sea revealed that the 2014 NAT earthquake was associated by post-seismic motion. A first evidence of this post-seismic motion was given in previous studies which analyzed seven days of data after the earthquake and reported that the deformation evolved for two days after the event (Sboras et al, 2015;Bitharis et al, 2016). In this study we revealed a detailed pattern of the postseismic deformation by analyzing data up to eight years after the earthquake.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The analysis of the GPS data from the stations in the North Aegean Sea revealed that the 2014 NAT earthquake was associated by post-seismic motion. A first evidence of this post-seismic motion was given in previous studies which analyzed seven days of data after the earthquake and reported that the deformation evolved for two days after the event (Sboras et al, 2015;Bitharis et al, 2016). In this study we revealed a detailed pattern of the postseismic deformation by analyzing data up to eight years after the earthquake.…”
Section: Discussionsupporting
confidence: 53%
“…Saltogianni et al (2016) investigated the dynamic displacements of GPS stations during the event by analyzing 1 Hz GPS data and found a correlation between the kinematic and the static displacements. Sboras et al (2015) and Bitharis et al (2016) studied the time-series of the GPS station in Samothrace and concluded that the displacement was not instantaneous during the earthquake, but it was stabilized after approximately two days. Tiryakioglu et al (2017) estimated inter-seismic velocities for 12 GPS stations on either side of NAF in Turkey using a period of about 6 years before the 2014 earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…Closest to epicentre is 018B GNSS station which located on the island of Samothrace and only 16 Km away. In order to evaluate the overall precision of PPP and consequently the site displacements, the daily solutions and not the epoch kinematic of every 5 minutes, were compared with those derived from network adjustment using the GAMIT software (Sboras et al, 2015;Bitharis et al, 2016). Coordinate comparisons of 018B station (epicentre) are illustrated in figures 3a and 3b for North, East and Up component respectively.…”
Section: The Applied Ppp Methods For Seismic Displacements Estimationmentioning
confidence: 99%
“…Relative positioning is highly Figure 1. Earthquake activity in 24 May 2014 between islands Lemnos and Samothraki NE of Greece accurate, and commonly used in Earth sciences (Bitharis et al, 2016). A type of a standalone point positioning techniques available in post process is the Precise Point Positioning (PPP).…”
Section: Tec Values Estimation Using Gnss Datamentioning
confidence: 99%